Effect of Immunosuppressive Drugs on the Changes of Serum Galactose-Deficient IgA1 in Patients with IgA Nephropathy - Kim, Min Jeong (PLoS One, 2016)
Galactose-deficient IgA1 (Gd-IgA1) and IgA-IgG complexes are known to play an important role in the pathogenesis of IgA nephropathy (IgAN). We aimed therefore to determine the impact of immunosuppression on the serum levels of Gd-IgA1, total IgA1 and IgA-IgG complexes in IgAN patients. In a retrospective study, serum samples from IgAN patients collected before transplantation (t(0)) and at 3- and 6-month posttransplant (t(3) & t(6)) were used to measure the levels of Gd-IgA1, total IgA1 and IgA-IgG complexes. The area under the curves (AUC) of immunosuppressants was calculated by the plot of plasma trough level or dosage of each immunosuppressant versus time and was interpreted as the extent of drug exposure. Thirty-six out of 64 IgAN patients, who underwent kidney transplantation between 2005 and 2012, were enrolled. From t(0) to t(3), serum Gd-IgA1 and total IgA1 decreased significantly (24.7 AU (18.6–36.1) to 17.2 (13.1–29.5) (p<0.0001); 4.1 mg/ml (3.6–5.1) to 3.4 (3.0–4.1) (p = 0.0005)), whereas IgA-IgG complexes remained similar. From t(3) to t(6), Gd-IgA1 and IgA-IgG complexes significantly increased (17.2 AU (13.1–29.5) to 23.9 (16.8–32.0) (p = 0.0143); OD 0.16 (0.06–0.31) to 0.26 (0.14–0.35) (p = 0.0242)), while total IgA1 remained similar. According to median regression analysis, AUC of prednisone t(0-6) was significantly associated with the decrease of Gd-IgA1 t(0-6) (P = 0.01) and IgA1 t(0-6) (p = 0.002), whereas AUC of tacrolimus t(0-6) was associated with the decrease of IgA1 t(0-6) (p = 0.02). AUC of prednisone t(0-3) was associated with the decrease of IgA-IgG complexes t(0)-(3) (p = 0.0036). The association of AUC prednisone t(0-6) with Gd-IgA1 t(0-6) remained highly significant after adjustment for other immunosuppressants (p = 0.0036). Serum levels of Gd-IgA1, total IgA1 and IgA-IgG in patients with IgAN vary according to the changing degrees of immunosuppression. The exposure to prednisone most clearly influenced the serum levels of Gd-IgA1.